Diagnostic utility of melanin production by fungi: Study on tissue sections and culture smears with Masson-Fontana stain - Challa Sundaram; G Uppin Shantveer; Pamidi Umabala; Vemu Lakshmi (Wolters Kluwer Medknow Publications, 2014)
Background: Dematiaceous fungi appear brown in tissue section due to melanin in their cell walls. When the brown color is not seen on routine H and E and culture is not available, differentiation of dematiaceous fungi from other fungi is difficult on morphology alone. Aims and Objective: To study if melanin production by dematiaceous fungi can help differentiate them from other types of fungi. Materials and Methods: Fifty tissue sections of various fungal infections and 13 smears from cultures of different species of fungi were stained with Masson Fontana stain to assess melanin production. The tissue sections included biopsies from 26 culture-proven fungi and 24 biopsies of filamentous fungi diagnosed on morphology alone with no culture confirmation. Results: All culture-proven dematiaceous fungi and Zygomycetes showed strong positivity in sections and culture smears. Aspergillus sp showed variable positivity and intensity. Cryptococcus neoformans showed strong positivity in tissue sections and culture smears. Tissue sections of septate filamentous fungi (9/15), Zygomycetes (4/5), and fungi with both hyphal and yeast morphology (4/4) showed positivity for melanin. The septate filamentous fungi negative for melanin were from biopsy samples of fungal sinusitis including both allergic and invasive fungal sinusitis and colonizing fungal balls. Conclusion: Melanin is produced by both dematiaceous and non-dematiaceous fungi. Masson-Fontana stain cannot reliably differentiate dematiaceous fungi from other filamentous fungi like Aspergillus sp; however, absence of melanin in the hyphae may be used to rule out dematiaceous fungi from other filamentous fungi. In the differential diagnosis of yeast fungi, Cryptococcus sp can be differentiated from Candida sp by Masson-Fontana stain in tissue sections.